Dietary supplementation of fenugreek (Trigonella foenum-graecum) seed as an alternative to antibiotics on growth performance and health of broiler chickens (Asian Journal of Medical and Biological Research, 2025)
Growing concerns over the use of antibiotics in poultry production have led to increased exploration of natural feed additives with health-promoting benefits. This study aimed to assess the impact of fenugreek seed (Trigonella foenum-graecum) supplementation in broiler diets as a potential substitute for antibiotic growth promoters. Conducted over a 28-day period (May 8 to June 5, 2019) at the Sher-e-Bangla Agricultural University Poultry Farm in Dhaka, the trial involved 150 Cobb 500 day-old broiler chicks. The birds were distributed randomly across five dietary groups, each with three replicates containing 10 chicks. The treatment groups included a control (no additive), an antibiotic-supplemented diet, and diets supplemented with fenugreek seed at 1%, 1.5%, and 2% inclusion levels. The findings revealed a significant (P0.05) were observed in the relative weights of internal organs or immune tissues. Blood cholesterol levels significantly decreased in the fenugreek-fed groups, while glucose levels remained unchanged. Hematological profiles improved notably in treated birds, particularly in hemoglobin concentration, red and white blood cell counts, and lymphocyte percentages. Microbial analysis showed that fenugreek supplementation reduced pathogenic bacteria such as E. coli and Salmonella, while promoting beneficial Lactobacillus populations. Additionally, antibody titers against Newcastle disease were significantly higher (P